PERANAN ETIKA APARATUR SIPIL NEGARA DALAM PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL (DISDUKCAPIL) KOTA BANDAR LAMPUNG - Refly Setiawan (Universitas Bandar Lampung (UBL), 2016)
In the public administration study, the regulation of the state civil administrative ethics is often called the code of conduct civil servants is the provisions or standards that regulate moral behavior of the apparatus / PNS. State civil apparatus ethics contains moral teaching and principles of good conduct for officials / civil servants in the discharge of duties and perform the functions of office. This research aims to determine the role of ethics in the state civil officials in the public service of population and civil registration department (Disdukcapil) Bandar Lampung. The research method used in this study is a qualitative research method. Where researcher went to the field to obtain data from the beginning to the end of the study. Sources and types of data used are primary data and secondary data. Methods of data collection by library research, observation, interviews and documentation. The results of this research indicate that the application of ethics in the state civil apparatus of population and civil registration department (Disdukcapil) Bandar Lampung is considered good enough. This is because they are in the public service not yet fully apply the ethical and in accordance with established procedures that are still in need monitoring either of the organizers of public services as well as from the public as users of public services and the role of ethics in the conduct of public service in population and civil registration department (Disdukcapil) Bandar Lampung.Keywords: The role of ASN ethics, public service